2023
DOI: 10.24875/gmm.m21000626
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of MLH1 promoter methylation mediated by gender and age in colorectal tumors from Mexican patients

Abstract: Introduction:Several genes determine the development of colorectal cancer (CRC), such as MLH1, which encodes a protein that participates in DNA repair. MLH1 hypermethylation has been associated with gene silencing. Objective: To analyze the methylation of five regions of MLH1 CpG island in colorectal tumors from Mexican patients. Materials and methods: One hundred and one tumor tissue samples were obtained from Mexican patients with CRC who provided informed consent. DNA was subjected to bisulfite conversion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…No previous studies had been conducted on the relationship between MSI-H tumors and age. A large sample study of unresectable or metastatic solid tumors in Japan examined the proportion of MSI-H in all tumors and found that the proportion was higher in patients aged less than 40 years than those aged over 80 years ( 7 ) The reason for the high proportion of MSI-H in patients aged over 80 years may be related to the occurrence of MLH1 promoter methylation ( 8 ). The high proportion of MSI-H in young patients may be related to genetic factors, and it is possible that these patients have Lynch syndrome or dMMR syndrome ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies had been conducted on the relationship between MSI-H tumors and age. A large sample study of unresectable or metastatic solid tumors in Japan examined the proportion of MSI-H in all tumors and found that the proportion was higher in patients aged less than 40 years than those aged over 80 years ( 7 ) The reason for the high proportion of MSI-H in patients aged over 80 years may be related to the occurrence of MLH1 promoter methylation ( 8 ). The high proportion of MSI-H in young patients may be related to genetic factors, and it is possible that these patients have Lynch syndrome or dMMR syndrome ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the methylation threshold is purely statistical using p values, or if it is a differential change measured in a percent difference, has not yet been sufficiently documented or validated. Many studies focus on single-gene associations with methylated CpG or DMR, some taking clinical data into context [ 67 , 68 ]. The genomic region of DMR and the impact on gene expression has also been studied, showing that DMRs on promoter regions adversely affect gene function [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%